Radiation-induced autophagy: mechanisms and consequences. (3rd March 2016) - Chaurasia, Madhuri; Bhatt, Anant Narayan; Das, Asmita; Dwarakanath, Bilikere S.; Sharma, Kulbhushan
ABSTRACT: Autophagy is an evolutionary conserved, indispensable, lysosome-mediated degradation process, which helps in maintaining homeostasis during various cellular traumas. During stress, a context-dependent role of autophagy has been observed which drives the cell towards survival or death depending upon the type, time, and extent of the damage. The process of autophagy is stimulated during various cellular insults, e.g. oxidative stress, endoplasmic reticulum stress, imbalances in calcium homeostasis, and altered mitochondrial potential. Ionizing radiation causes ROS-dependent as well as ROS-independent damage in cells that involve macromolecular (mainly DNA) damage, as well as ER stress induction, both capable of inducing autophagy. This review summarizes the current understanding on the roles of oxidative stress, ER stress, DNA damage, altered mitochondrial potential, and calcium imbalance in radiation-induced autophagy as well as the merits and limitations of targeting autophagy as an approach for radioprotection and radiosensitization.